IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF STRUCTURAL APPROACH NUMBERED HEADS TOGETHER TO IMPROVE STUDENTS’ MATH ACHIEVEMENT AT CLASS VII HANG JEBAT JUNIOR HIGH SCHOOL 1 PEKANBARU - Syaila Affani; Titi Solfitri; Nahor Murani Hutapea (Jurnal Prinsip Pendidikan Matematika, 2021)
This research is a classroom action research that aims to improve the learning process and improve students’ mathematics learning outcomes through the application of cooperative learning models with the structural approach of NHT. This research was conducted in class VII Hang Jebat Junior High School 1 Pekanbaru in the 2019/2020 school year. The subjects of this study were 31 students consisting of 16 male students and 15 female students. The study was conducted in two cycles with each cycle consisting of three meetings and one daily repetition. The research instrument used was a learning device and data collection instrument. Learning tools consisting of the syllabus, learning implementation plan, student worksheet, and NHT question sheets. Data collection instruments consisted of observation sheets and test results of learning. Based on qualitative data analysis, it was concluded that there was an improvement in the learning process after applying the cooperative learning model of the structural approach Numbered Heads Together. Quantitative descriptive analysis shows the improvement in students’ mathematic scores. Based on the results of the study it can be concluded that the application of the cooperative learning model of the Numbered Heads Together structural approach can improve the learning process and can improve the learning outcomes of students in grade VII Hang Jebat Junior High School 1 Pekanbaru.